Direct visualization of intracranial aneurysms by multiplane dynamic CT. - Vonofakos, D; Hacker, H; Grau, H (American Journal of Neuroradiology, 1983)
Using an intravenous injection of 100-150 ml contrast medium (flow, 1-1.5 ml/sec) adjacent 2-mm-thick cuts are scanned at the level of the circle of Willis. After highlighting and multilevel image summation a complete picture of the vascular anatomy of the base of the brain is obtained. In this way aneurysms as small as 2-3 mm in diameter can be detected. The method has high reliability, as indicated by the results in 31 cases.